Mutations in the rpoB Gene of Multidrug-Resistant Mycobacterium tuberculosis Isolates from Brazil - Valim, Andréia Rosane M. (American Society for Microbiology, 2000)
Mutations in a 69-bp region of the rpoB gene associated with rifampin resistance (Rif(r)) in 100 isolates (82 Rif(r)) from three states of Brazil were studied. Twenty-one different kinds of mutations were identified in the Rif(r) isolates, and six new alleles are described.